New Zealand : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1996)
This paper reviews economic developments in New Zealand during 1992-95. According to the production measure, growth began to pick up in the middle of 1991, rising to about 3 percent in 1992/93, before jumping to nearly 6 percent in each of 1993/94 and 1994/95. Although export performance remained strong, the net contribution of the external balance turned negative in 1992/93-1994/95, as imports of capital goods surged in line with the expansion of investment. Gross fixed capital formation increased by 23 percent in real terms in 1994/95.